Educação permanente em saúde : representações sociais de enfermeiros da saúde da família - Formenton, Yaisa França (2013)
One of the main challenges faced by Family Health Strategy to change the model of care is the lack of professionals trained to this role in SUS. The Permanent Health Education is a tool that can lead to qualification in health care and a new logic in the process of health work. In this context, the educational role of nurses is strengthened, and the identification Social Representations education that permeate their educational practices aiming changes or stays in health care become relevant. To Understand the Social Representation of Continuing Education of Health Family nurses; analyze how their educational action influence in work processes and identify strengths and weaknesses in the actions of these Nurses. Qualitative research through semi-structured interviews with nurses from the Family Health of small towns in the Heart Region of DRIII Araraquara - SP. After interviews transcription, the contents were analyzed by comparing the thematic category and lexical analysis by software ALCESTE by using the Permanent Health Education references, Work Process and Social Representations. Four categories were made: 1) Influence of Permanent Education in the work process where fragmentation and professional specialty remains the focus of educational activities; 2) The Centralization of nurses in the actions of Continuing Education in where this role have been seen in two ways, one group recognizes that this their role and others consider that it should be shared with the team; Different conceptions of Continuing Education where the education to update knowledge is hegemonic, showing some movements leading to a conception of education to change the work process, and 4) Difficulties in perfoming educational activities characterized by low motivation of the time and lack of time to carry out the activities. The Social Representation Continuing Education for this group is based in the notion of traditional education, although although it is possible identify some movements that approximate the logic of Permanent Health Education, which may lead to a transformation of the representation.